2004
DOI: 10.1186/1472-6793-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases endostatin in circulation of healthy volunteers

Abstract: Background: Physical inactivity increases the risk of atherosclerosis. However, the molecular mechanisms of this relation are poorly understood. A recent report indicates that endostatin, an endogenous angiostatic factor, inhibits the progression of atherosclerosis, and suggests that reducing intimal and atherosclerotic plaque tissue neovascularization can inhibit the progression atherosclerosis in animal models. We hypothesize that exercise can elevate the circulatory endostatin level. Hence, exercise can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 32 publications
3
19
1
1
Order By: Relevance
“…Some researchers have reported minor, time dependent fluctuations in the arterial-venous difference in plasma endostatin levels, but no change in tissue endostatin levels, following an acute exercise bout (787). Others have reported increases in circulating endostatin in response to exercise (322, 893), although muscle levels of endostatin decrease after exercise training (323). Endostatin levels are increased in skeletal muscle of diabetic patients compared to non-diabetic controls (873), suggesting that endostatin may play a role in maintaining an angiostatic environment in the muscle of diabetic patients.…”
Section: Training Adaptations Within the Active Muscle: Increased mentioning
confidence: 99%
“…Some researchers have reported minor, time dependent fluctuations in the arterial-venous difference in plasma endostatin levels, but no change in tissue endostatin levels, following an acute exercise bout (787). Others have reported increases in circulating endostatin in response to exercise (322, 893), although muscle levels of endostatin decrease after exercise training (323). Endostatin levels are increased in skeletal muscle of diabetic patients compared to non-diabetic controls (873), suggesting that endostatin may play a role in maintaining an angiostatic environment in the muscle of diabetic patients.…”
Section: Training Adaptations Within the Active Muscle: Increased mentioning
confidence: 99%
“…As Van Craenenbroeck et al (24) showed, the serum levels of VEGF increased after acute exercise. On the other hand, Suhr et al (14) reported no change in serum VEGF following acute exercise while Gu et al (25) reported a decrease in serum VEGF concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study revealed increased VEGF levels for sprint-endurance training groups without supplementation, which are consistent with the results of some studies 23,25,28 while different from the results of some other studies. 8,29 The specific training method applied in this study could account for such contradictory results. In addition to the aforesaid training method, different timings of the blood sample collection may also account for the contradictory results of the present study and the study conducted by Thorell et al 17 In fact, in the latter study blood sampling was performed 1 hour after exercise, whereas in the present study blood samples were collected 24 hours after the last training session and in the morning on an empty stomach.…”
Section: Discussionmentioning
confidence: 99%
“…8,27 In addition, Gu et al reported reduced serum VEGF concentration after exercise. 29 Several studies have also contemplated the effect of free radicals on angiogenesis. Zhao et al, analyzing the effect of reactive oxygen species (ROS) on cardiac angiogenesis following myocardial infarction (MI), found that angiogenesis occurs in the first week of MI, developed in spatio-temporal symmetry with ROS.…”
mentioning
confidence: 99%